The Human RNA Helicase DDX21 Presents a Dimerization Interface Necessary for Helicase Activity - Maria J. Marcaida; Annamaria Kauzlaric; Alice Duperrex; Jenny Sülzle; Martin C. Moncrieffe; Damilola Adebajo; Suliana Manley; Didier Trono; Matteo Dal Peraro (iScience, 2020)
Summary: Members of the DEAD-box helicase family are involved in all fundamental processes of RNA metabolism, and as such, their malfunction is associated with various diseases. Currently, whether and how oligomerization impacts their biochemical and biological functions is not well understood. In this work, we show that DDX21, a human DEAD-box helicase with RNA G-quadruplex resolving activity, is dimeric and that its oligomerization state influences its helicase activity. Solution small-angle X-ray scattering (SAXS) analysis uncovers a flexible multi-domain protein with a central dimerization domain. While the Arg/Gly rich C termini, rather than dimerization, are key to maintaining high affinity for RNA substrates, in vitro helicase assays indicate that an intact dimer is essential for both DDX21 ATP-dependent double-stranded RNA unwinding and ATP-independent G-quadruplex remodeling activities. Our results suggest that oligomerization plays a key role in regulating RNA DEAD-box helicase activity.